1995
DOI: 10.1002/jbm.820290406
|View full text |Cite
|
Sign up to set email alerts
|

Glass Wool–H2O2/CoCl2 test system for in vitro evaluation of biodegradative stress cracking in polyurethane elastomers

Abstract: Environmental stress cracking (ESC) in polyetherurethanes has been demonstrated in animal models. However, duplication of this phenomenon in vitro has been a challenge. The glass wool-H2O2/CoCl2 test system was designed to provide oxidation components found in vivo, i.e., hydroxyl radical (HO.), molecular oxygen (O2), and superoxide (O2-.) required for auto-oxidation of polyetherurethanes. The in vitro test is not only reliable in duplicating the characteristics of in vivo stress cracking in polyetherurethanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 15 publications
3
82
0
Order By: Relevance
“…Immune cells attack implants in vivo by releasing ROS that are not present in a saline solution. Previous work has simulated in vivo degradation in the presence of these chemicals by including hydrogen peroxide (Meijs et al 1993, Yokoyama et al 2007, Patrick et al 2011 or generating reactive species in situ via the reaction of hydrogen peroxide with the metal ions in aging protocols (Ali et al 1993, Zhao et al 1995. One of the challenges of including ROS is their short lifetimes.…”
Section: Reactive Accelerated Aging Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune cells attack implants in vivo by releasing ROS that are not present in a saline solution. Previous work has simulated in vivo degradation in the presence of these chemicals by including hydrogen peroxide (Meijs et al 1993, Yokoyama et al 2007, Patrick et al 2011 or generating reactive species in situ via the reaction of hydrogen peroxide with the metal ions in aging protocols (Ali et al 1993, Zhao et al 1995. One of the challenges of including ROS is their short lifetimes.…”
Section: Reactive Accelerated Aging Systemmentioning
confidence: 99%
“…However, this approach alone may not adequately capture the aggressive chemical environment that is created by activated immune cells, which release digestive enzymes and reactive oxygen species (ROS) (Badwey and Karnovsky 1980, Halliwell 1992, Polikov et al 2005, Freinbichler et al 2011, Patrick et al 2011. In our system, we have included hydrogen peroxide to mimic the effect of ROS generation during the brain's injury response (Ali et al 1993, Zhao et al 1995, Patrick et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In compliance with the literature, 21,22 hydrogen peroxide was selected as the oxidizing agent while simultaneous oxidative and acidic conditions were reproduced using an HNO 3 solution, the only acidic medium described in the literature as being able to discriminate between various polyurethanes. 31 The samples were immersed in a solution containing either 20% (w/v) H 2 O 2 or 0.5N HNO 3 during periods ranging from 0 to 21 days, due to the rather aggressive nature of these solutions.…”
Section: Aging Of the Specimensmentioning
confidence: 99%
“…18 Several attempts have been made to reproduce chemical oxidation in vitro [19][20][21] but with contradictory or limited results unless under strong or sophisticated operating conditions. 22 Moreover, the enzymatic and oxidative degradation in vitro has not yet led to clear and unequivocal results as the dynamic in vivo conditions are difficult to reproduce in static in vitro experiments. [23][24][25][26][27][28][29][30] Within the polyurethane family of polymers, polyether urethanes and polycarbonate urethanes both have been shown to present better in vitro and in vivo chemical stability compared to polyesterurethanes.…”
Section: Introductionmentioning
confidence: 99%
“…Many years of use and testing of the Pellethane 2636 series of PTMO-based polyurethanes has shown that P80A is far more susceptible to environmental stress cracking (ESC) in vivo, and its biostability performance more process-sensitive than its harder counterpart, P55D. [17][18][19][20]35 Figure 1 shows scanning electron micrographs of explanted P80A and P55D polymers after a strained (150% strain) 3-month subcutaneous implantation in sheep in our laboratories. The P80A shows evidence of deep surface cracks where as P55D shows no visible signs of degradation.…”
Section: Introductionmentioning
confidence: 99%